Migration, Gender, and Integration: Syrian Women's Experiences in Türkiye - Yanik Aslan, Sibel (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
The global phenomenon of migration in the 21st century, often referred to as the